PELAKSANAAN KURIKULUM MUATAN LOKAL PADA SMK NEGERI DI KABUPATEN MAJENE - Thamrin, Thamrin (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2014)
The regulation of the Ministry of National Education Number 22 year 2006 concerning content standard stated that the local content is an integral part of the structure of curriculum at the level of elementary and secondary education. Based on the fact that Indonesia is a unity state which consist of a variety of distric with various geographical condition, natural sources, and its people (human resources) with different history backgrounds and culture. The development of local content curriculum in public vocational School in Majene distric focuses on the internal and external supports, thedecision of the types lokal content, and the supporting and inhibiting fktors in the development process of local content curriculum, so this study aims at analyzing the development, the determination as well as the supporting and inhibiting factor on the implementation of local content curriculum in public vocation schools in Majene district.The study is a descriptive research which reveals the problem solving of the main problems based on the data and obtained documents. The study was conducted in in public vocation schools in Majene district. The focus of the study was the development of department as well as the supporting and inhibiting factors on the implementation of local content curriculum in public vocation schools in Majene district. The instruments used in the study were interview and observation. Data were collected using observation technique, interview techniques, documentation technique, analyzing data arrangement, and classification of data. Data processing was conducted to test the hypothesis which had been formulated. Descriptive analysis was conducted to discover the description of data based on each variable to draw conclusions.The results of the study reveal that the development process of local content curriculum in public vocation schools in Majene district was not approriate with the technical procedure of the development of local content curriculum for vocational school 2010. In determining the types of subjects which contain the local content, the Vocational Schools in Majene generally decided directly without appropriate procedure, but it was based on the needs and the interest of the schools. The inhibiting factors was lack of participation from the people and parents in giving some thoughs in education. Moreover, lack of fasility and infrastructure, lack of evaluation on curriculum, teachers, competence which not appropriate to the subject matter made the objective of the study unachievable.